In vitro growth of phalaenopsis H-Sin sunflower in different media and pH levels - Albuquerque Donha, Riviane Maria [UNESP]; Fadin, Dauri Aparecido; Massaro, Raquel; Gianini, Patrícia Franco; Pedroso-De-Moraes, Cristiano (Centro Universitario de Maringa, 2019)
Orchids have significant ornamental and commercial values. Phalaenopsis H-Sin Sunflower is a highly appreciated species, worldwide, with significant market value. However, Orchidaceae have slow vegetative development and require specific needs which raises their production costs due to alternative technique employed in their growth. In vitro seeding is an important tool for main orchid species. Current study analyzes in vitro growth aspects of Phalaenopsis H-Sin Sunflower by evaluating the effects of culture medium 1/2MS and in two media based on commercial fertilizers Hyponex® (NPK 6,5-6-19) and Kristalon orange® (NPK 6-12-36), at three pH levels (5.3, 5.8, 6.3). Seeds were distributed in four flasks with different media. After 180 days, twenty seedlings were randomly removed from each flask for statistical analysis. Data comprised height of plants (HP), length of larger root (LLR), length of the biggest leaf (LBL), number of roots (NR), weight of fresh mass ( WFM) and weight of dry mass ( WDM). Results show that the most efficient medium in the growth of Phalaenopsis H-Sin Sunflower seedlings was Hyponex®, at pH 5.3, with the greatest averages for all variables.
Crescimento in vitro de Phalaenopsis H-Sin Sunflower em diferentes meios de cultura e níveis de pH
Keywords: Agribusiness; In vitro propagation; Orchidaceae